2014
DOI: 10.1039/c3sc53187b
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic tris-cyclometalated platinum(iv) complexes: a new class of long-lived, highly efficient 3LC emitters

Abstract: Tris-cyclometalated Pt(IV) complexes are reported for the first time. The facial isomers exhibit long-lived 3LC emissions with quantum yields up to 0.49, the highest ever found for Pt(IV) complexes, combined with a strong oxidizing character in the excited state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 73 publications
11
100
0
Order By: Relevance
“…To illustrate this, the absorption spectra of mer ‐ 3 ac and mer ‐ 3 ad are compared in Figure 3 with those of 2 a and 2 c , or 2 a and 2 d , respectively, which can be taken as representative of the absorptions of each cyclometalating ligand. The absorption bands of fac ‐ 3 ab are sharper and of slightly higher energies compared with mer ‐ 3 ab , just as observed for the homoleptic derivatives mer / fac ‐ 3 a and b 15. None of the complexes exhibit solvatochromic absorptions, which suggests that the involved electronic transitions have little or no charge‐transfer character.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…To illustrate this, the absorption spectra of mer ‐ 3 ac and mer ‐ 3 ad are compared in Figure 3 with those of 2 a and 2 c , or 2 a and 2 d , respectively, which can be taken as representative of the absorptions of each cyclometalating ligand. The absorption bands of fac ‐ 3 ab are sharper and of slightly higher energies compared with mer ‐ 3 ab , just as observed for the homoleptic derivatives mer / fac ‐ 3 a and b 15. None of the complexes exhibit solvatochromic absorptions, which suggests that the involved electronic transitions have little or no charge‐transfer character.…”
Section: Resultsmentioning
confidence: 62%
“…We have previously shown that the reactions of bis‐cyclometalated precursors of the type [Pt(C^N) 2 Cl 2 ] with AgOTf (2 equiv) and an excess of the N^CH ligand in non‐coordinating solvents give mer isomers of homoleptic tris‐cyclometalated Pt IV complexes mer ‐[Pt(C^N) 3 ]OTf (C N=ppy, tpy, dfppy, ppz) (Scheme ) 15. The corresponding strongly emissive fac isomers were obtained by photoisomerization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The complexes contained bis-cyclometalating (C^N) ligands of the general formula Pt(C^N) 2 (CH 2 Cl)Cl and were prepared by a photooxidative addition of CH 2 Cl 2 onto the corresponding bis-cyclometalated Pt(II) parental complexes. Although Pt(IV) complexes have attracted great attention in cancer therapy [104106], only in the very recent past they are receiving increasing interest as luminescent compounds [107108]. Such derivatives are characterized by long-lived triplet-manifold π–π* excited states with either 3 LC or 3 ILCT nature.…”
Section: Reviewmentioning
confidence: 99%